Fumonisins: Impact on Agriculture, Food, and Human Health and their Management Strategies - Madhu Kamle; Dipendra K. Mahato; Sheetal Devi; Kyung Eun Lee; Sang G. Kang; Pradeep Kumar (Toxins, 2019)
The fumonisins producing fungi, Fusarium spp., are ubiquitous in nature and contaminate several food matrices that pose detrimental health hazards on humans as well as on animals. This has necessitated profound research for the control and management of the toxins to guarantee better health of consumers. This review highlights the chemistry and biosynthesis process of the fumonisins, their occurrence, effect on agriculture and food, along with their associated health issues. In addition, the focus has been put on the detection and management of fumonisins to ensure safe and healthy food. The main focus of the review is to provide insights to the readers regarding their health-associated food consumption and possible outbreaks. Furthermore, the consumers’ knowledge and an attempt will ensure food safety and security and the farmers’ knowledge for healthy agricultural practices, processing, and management, important to reduce the mycotoxin outbreaks due to fumonisins.